Optimising DOS Attacks Using Machine Learning Algorithms and Securing IOT Devices from Attacks - Siwal, Rahul; P, Sivakumar (2024 International Conference on Expert Clouds and Applications (ICOECA), 2024)
In today's hyperconnected world, identifying and defending against denial-of-service (DoS) attacks and securing Internet of Things (IoT) devices are increasingly crucial. Recognizing distributed denial-of-service (DDoS) attacks is essential for network security enhancement and IoT device security. This research explores various methods to mitigate the impact of DDoS attacks, aiming to reduce the likelihood of such attacks. We intend to employ machine learning strategies such as the Random Forest Algorithm, ADAboost, Blockchain, Gradient Boost, and Extra Tree Algorithm to prevent malicious network traffic from overloading servers and causing outages. The initiative offers significant advantages, particularly in theory and statistics. We will test our system using the NSL _ KDD dataset, initially training the data and then subjecting it to a series of tests. Data will be presented using tables, graphs.